STRATEGI KOMUNIKASI KESEHATAN PENANGANAN STUNTING (Studi Pada Kelurahan Watang Bacukiki Kota Parepare) - Alif, Insyirah Salsabila; Karnay, Sudirman; Amir, Andi Subhan (Interaksi: Jurnal Ilmu Komunikasi, 2023)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition so that children become too short compared to children of their age. Until mid-2022, Watang Bacukiki Village is included in the five sub-districts with the highest cases of stunting in Parepare City. This study aims to describe the communication strategy implemented by the Watang Bacukiki Village in an effort to deal with stunting through balanced nutrition persuasive communication. This research is descriptive-qualitative in nature and the determination of research subjects is based on purposive sampling. Based on the research that has been done, the results show that the communication strategy implemented by the Watang Bacukiki Village in efforts to deal with stunting is by implementing four core stages in the preparation of a communication strategy, namely: (1) assigning communicators, (2) determining audiences, (3) compiling messages, and (4) choosing media and communication channels. Apart from that, Watang Bacukiki Village also presented innovative programs to support the acceleration of zero stunting.